Estudo da densidade, forma e configuração espacial em campus: análise do Campus I da Universidade Federal da Paraíba - Félix, Lílian Leite (2019)
This research deals with the analysis of density, building shape and spatial configuration, applied on a university campus, in order to achieve a new reading of space. Such criteria, little investigated in campuses analysis are explored by the Spacemate / Spacematrix method, through a quantitative-qualitative approach, applied as a tool capable of diagnosing these characteristics on campus. The analytical application was applied on campus I of the Federal University of Paraiba, in the city of João Pessoa, Brazil. Compared to small urban centers for being provided with an infrastructure network, campuses have been the subject of study regarding the application of design principles linked to sustainability through the implementation of environmental management systems, sustainable buildings and the use of space analysis as a tool to investigate the mobility and quality of life of local users. Thus, it is possible to contribute to the study corpus by adopting a little explored research axis. The results of the analysis reveal a formal configuration equivalent to urban areas with low utilization rates, low-profile buildings and wide-open spaces. Therefore, it is possible to establish a relationship between elements that promote the sustainability of the city, such as density, building shape and spatial configuration, within a scenario of university campuses, in addition to promoting the continuity of a more in-depth study under the mentioned aspects.